Individualized mRNA vaccines evoke durable T cell immunity in adjuvant TNBC - U. Sahin; M. Schmidt; E. Derhovanessian; A. Cortini; I. Vogler; T. Omokoko; E. Godehardt; S. Attig; S. Newrzela; J. Grützner; N. Bidmon; S. Bolte; et al. (Nature, 2026)
Abstract Triple-negative breast cancer (TNBC) is frequently associated with metastatic relapse, even at an early stage 1 . Here we assessed an individualized neoantigen mRNA vaccine in 14 patients with TNBC following surgery and after neoadjuvant or adjuvant therapy. In peripheral blood of nearly all patients, high-magnitude, vaccine-induced, mostly de novo T cell responses to multiple neoantigens were detected that remained functional for several years. Characterization of individual patients revealed that a large proportion of these T cells developed into two subsets: a late-differentiated phenotype with markers indicative of ‘ready-to-act’ cytotoxic effector T cells, and T cells with a stem cell-like memory phenotype. Eleven patients remained relapse-free for up to six years post-vaccination. Recurrence occurred in three patients: the individual with the weakest vaccine-induced T cell response relapsed, but achieved complete remission on subsequent anti-PD-1 therapy; another patient had a tumour with low major histocompatibility complex (MHC) class I expression with MHC class I-deficient cells growing out under vaccination; and the third patient was BRCA-positive and had a recurrence from a genetically distinct primary tumour. These findings demonstrate the feasibility of individualized RNA vaccines in TNBC, document persistence of vaccine-induced, functional neoantigen-specific T cells and provide insights into possible immune escape mechanisms that will guide future approaches.